On Determination of the Relationship between Inflation and Real Savings in Kenya - Njoroge, Joyce; Simwa, Richard Onyino; Kimathi, Jane (International Journal of Research and Innovation in Social Science, 2025)
This study investigates the relationship between inflation and real savings in Kenya over the period 2013–2024. Using time series econometric methods, including the Augmented Dickey-Fuller (ADF) test for stationarity, Granger causality to determine direction of influence, and Ordinary Least Squares (OLS) regression for estimation, the study examines how inflation dynamics affect savings behavior. The results reveal that inflation inversely affects savings in the short run, with higher inflation rates being associated with lower levels of real savings. Specifically, inflation accounts for 28.1% of variations in real savings. These findings confirm a negative and statistically significant relationship between inflation and real savings, and thus highlights the importance of targeting low and stable inflation rate management strategies to attract increased incentives for investors to save, with respect to the Kenyan financial environment.
Journal article
Keywords: Augmented Dickey-Fuller; Ordinary Least Squares